Silang.ig Social Media (Start Up) Strategy in Creating Disability-Friendly Online Access for Deaf - Irniyati Samosir (International Seminar on Social Work Update, 2023)
People with disabilities, especially deaf people are close to us. Communities often have difficulty interacting with them. Deaf people often experience obstacles in accessing various information because of the unavailability of services/facilities related to deaf culture in public places and public services. The background of this research is to find out how the social media (startup) strategy of silang.ig creates bold access ti problems. The purpose of this study is to describe the efforts made to please deaf people and the general public to receive information through the content produced. This research method uses a descriptive qualitative approach with data collection methods: in-depth interviews, observation, document study and data analysis through data collection, data reduction, data presentation and concluding. From the results of the research, it can be interpreted that the efforts and strategies of the silang.ig are quite helpful for deaf people and also hearing people in learning deaf culture, one of which is through Indonesian Sign Language (BISINDO)